Risk Factors for Stunting at Balung Health Center, Jember Regency, Indonesia - Agustin, Aisyiyah Alviana; Shodikin, Muhammad Ali (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Stunting is a condition of failure to thrive in children under five years of age as a result of chronic malnutrition so that the child is too short for his age. The prevalence rate of stunting in Indonesia is still above 20%, meaning that it has not reached the target. Factors that influence stunting include birth length and birth weight. The purpose of this study was to determine the description of the factors that influence the incidence of stunting in children aged 0-59 months in the working area of the Balung Public Health Center in 2021. This research is descriptive in nature which was conducted Stunting is a condition of failure to thrive in children under five years of age as a result of chronic malnutrition so that the child is too short for his age. The prevalence rate of stunting in Indonesia is still above 20%, meaning that it has not reached the target. Factors that influence stunting include birth length and birth weight. The purpose of this study was to determine the description of the factors that influence the incidence of stunting in children aged 0-59 months in the working area of the Balung Public Health Center in 2021. This research is descriptive in nature, which was conducted in the working area of Puskesmas Balung, Jember Regency in April 2021. The population is children under five with age stunting. 0-59 months recorded in the EPPGBM in February 2021. Sampling in this study was carried out by total sampling, namely as many as 639 stunting toddlers. Of the 639 stunted children under five, 347 were male and the majority occurred at the age of 12-23 months, namely 150 under five. From 639 toddlers, it describes 516 toddlers with normal body length and 123 toddlers with short birth lengths. Meanwhile, the birth weight of 639 children under five shows that 422 children under five were born with normal birth weight. From the data above, it can be concluded that the majority of children under five with stunting in the working area ofPuskesmas Balung were born with normal body length and weight. For this reason, it is necessary to carry out further research on the relationship of several risk factors using statistical tests. In addition, it is also necessary to look for other risk factors that can cause stunting in children.  Abstrak: Stunting adalah kondisi gagal tumbuh pada anak balita (bayi di bawah lima tahun) akibat dari kekurangan gizi kronis sehingga anak terlalu pendek untuk usianya. Angka prevalensi stunting di Indonesia masih di atas 20%, artinya belum mencapai target. Faktor yang mempengaruhi stunting diantaranya panjang badan lahir dan berat badan lahir. Tujuan penelitian ini adalah untuk mengetahui gambaran faktor yang mempengaruhi kejadian stunting pada balita usia 0-59 bulan di wilayah kerja Puskesmas Balung Tahun 2021. Penelitian ini bersifat deskriptif yang dilakukan di wilayah kerja Puskesmas Balung Kabupaten Jember pada bulan April 2021.  Populasi adalah balita stunting usia 0-59 bulan yang terdata pada EPPGBM pada bulan Februari 2021. Pengambilan sampel pada penelitian ini dilakukan dengan cara total sampling yaitu sebanyak 639 balita stunting. Dari 639 balita stunting, 347 berjenis kelamin laki-laki dan mayoritas terjadi pada usia 12-23 bulan yaitu sebesar 150 balita. Dari 639 balita menggambarkan 516 balita lahir dengan panjang badan normal dan 123 balita memiliki panjang badan lahir pendek. Sedangkan berat badan lahir 639 balita mengambarkan 422 balita lahir dengan berat bdan lahir normal. Dari data diatas dapat disimpulkan bahwa mayoritas balita stunting di wilayah kerja Puskesmas Balung ini lahir dengan kondisi panjang bdan dan berat badan normal. Untuk itu perlu dilakukan penelitian lebih lanjut mengenai hubungan beberapa faktor risiko tersebut dengan menggunakan uji statistik. Selain itu perlu juga dilakukan pencarian faktor risiko lain yang bisa menjadikan stunting pada anak.